Finding the Right Fit: Helping Students Apply Theory to Service-Learning Contexts. (March 2018) - Ricke, Audrey
Background: Although past studies of service-learning focus on assessing student growth, few studies address how to support students in applying theory to their service-learning experiences. Yet, the task of applying theory is a central component of critical reflections within the social sciences in higher education and often causes anxiety among undergraduate students.Purpose: This article identifies a pedagogical model that helps students navigate the selection and application of theory to their service-learning experiences.Methodology/Approach: The pedagogical model is based on a case study of an upper-division anthropology service-learning course, which included survey and interview data to assess the model's effectiveness.Findings/Conclusions: The findings indicate that a familiar framing analogy, combined with a specific set of scaffolded in-class activities that takes into consideration Perry's scheme of learning, is useful for bridging the gap between understanding theory and selecting and applying a particular theory to service-learning projects. Such an approach helped relieve student anxiety and confusion surrounding theory application and service-learning.Implications: To grow as scholars, students must be able to match theory to real-world situations on their own. By combining a framing analogy with scaffolded activities, instructors can help students transition from memorizing theories to applying them to their service-learning.